A matter of human right, not grace or discretion: Regulating working time in Hong Kong. (December 2015) - Wong, Kai Yeung
This article argues that China (on behalf of Hong Kong in the international arena) has been placed in breach of its obligations under the ICESCR for failing to protect employees from abuse and ensure that they work in just and favourable conditions which are reasonable in terms of working hours. Drawing upon treaties and jurisprudential materials emerging from the international and European organs whose task is to uphold socio-economic rights, the author delineates the content of the 'minimum core obligations' entailed by Article 7(d) of the ICESCR and the manner in which they have to be domestically implemented. The author then endeavours to underline the essential features a scheme regulating working hours in Hong Kong must include if it is to operate consistently with the ICESCR.